Model pembelajaran auditory, intellectually, and repetition untuk meningkatkan pemahaman konsep sumber energi pada peserta didik kelas iv sekolah dasar - Diana Permata Sari (Didaktika Dwija Indria, 2019)
Abstract. A purpose of this research is for intensify an understanding of concepts at the energy sources by applying learning models Auditory, Intellectually and Repetition for students in class IV of SD Negeri Tegalrejo No. 98 Surakarta. This study used classroom action research on 3 cycles that every cycles consisted of 4 innings composed  of planning, implementation, observation, & reflection. Subject from this reseacrh are students and teacher in class IV SD Negeri Tegalrejo No. 98 Surakarta as many 30 students. The reseachers as preceptor on this reseacrh. Data from this study is collect by teacher and students through surveilance, debriefing, documentation, & test. Data is validated by using content validity, source & technique triangulations. Data analyzed by using interactive analysis from Milles and Huberman and comparative descriptive. Posit on the result of this research, a conclusion is learning model Auditory, Intellectually and Repetition can improve the conceptual understanding for energy sources.      Keywords: conceptual understanding, energy sources, Auditory Intellectually and Repetition, elementary school